Biomarker-based diagnosis of mild cognitive impairment due to Alzheimer’s disease: how and what to tell. A kickstart to an ethical discussion - Porteri, Corinna; Frisoni, Giovanni B. (Frontiers in Aging Neuroscience, 2014)
New criteria for the diagnosis of Alzheimer’s disease (AD) based on biomarker results have recently been developed and are currently undergoing extensive validation. The next few years may represent a time window where the diagnostic validity of biomarkers will be studied in highly specialised research settings. Biomarkers results will be used to direct clinical diagnosis and, whenever appropriate, therapy and management. This piece aims to stimulate discussion by identifying the ethical challenges involved in the use of biomarkers to make a diagnosis of mild cognitive impairment due to AD and disclose it to patients. At the individual level, these challenges are related to i) the ethical appropriateness of implementing an ecological diagnostic research protocol, ii) the related informed consent process, and iii) the diagnostic disclosure. We justify the ethical legitimacy of implementing a research diagnostic protocol by referring to the respect of patients’ subjectivity and autonomy, and we suggest guidelines for informed consent development and diagnostic disclosure. All of the above points are discussed in light of the unique features of AD, currently scanty treatment options, and knowledge and uncertainties regarding the diag